DOI: 10.14201/gredos.149474
|View full text |Cite
|
Sign up to set email alerts
|

Diseño, desarrollo, implementación y evaluación del programa “E-Mentoring en programas de prácticas académicas”

Abstract: Mentoring is a practice that supports learning, experimentation and helps students in Higher Education to develop their potential. A mentoring relationship is one in which both the mentor and mentee, recognize the need for professional and personal development.participating academic programs. For such process, two parts have been developed, firstly, a pilot study for the validation of the e-mentoring program generated, in a Colombian university with students of academic internship of a Marketing program. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1
2

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 176 publications
0
4
1
2
Order By: Relevance
“…The particular results between the competencies by both participant groups in the pilot revealed positive results, especially in four distinctive competencies (project management, problem-solving, autonomous work, and teamwork), showing in each one, progressive improvement of their strength and quality, and it established improvements between the connection of the participants. These data are insufficient to prove that there is a trend in the ratings given by mentors and mentees, we found that there is no agreement between mentee and mentor scores, except for the problem-solving competency [32].…”
Section: Theoretical Implicationscontrasting
confidence: 59%
See 4 more Smart Citations
“…The particular results between the competencies by both participant groups in the pilot revealed positive results, especially in four distinctive competencies (project management, problem-solving, autonomous work, and teamwork), showing in each one, progressive improvement of their strength and quality, and it established improvements between the connection of the participants. These data are insufficient to prove that there is a trend in the ratings given by mentors and mentees, we found that there is no agreement between mentee and mentor scores, except for the problem-solving competency [32].…”
Section: Theoretical Implicationscontrasting
confidence: 59%
“…Mentoring seeks to build individual strengths, therefore, the philosophy of the program is dedicated to empowering participants to acquire professional competencies; this aspect is reflected in all elements designed for the pilot program, including its objectives; program materials and communications; orientation and training; and the interactions between program participants, program coordinator, mentors, and mentees [5]. Thus, the mentoring program is developed with the same objective as programs of this same nature, which, are delimited in playing a positive role in the initiation and retention of students in learning processes at the higher education level [9,19,32,41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations